Кореляційний аналіз когнітивних викликаних потенціалів у право- та ліворуких хлопців і дівчат середнього шкільного віку - Качинська, Тетяна Валеріївна; Абрамчук, Ольга Миколаївна; Kachynska, Tetiana V.; Abramchuk, Olha M. (Київський національний університет імені Тараса Шевченка, 2012)
Peculiarities of inter- and introhemispheric interactions of cognitive evoked potentials in persons with different type of manual asymmetry depending on sex factor and probability of target visual stimuli’s presentation were studied. Analysis of correlations showed that the more pronounced spatial synchronization biopotentials of the cerebral cortex characterized girls regardless with different type of manual asymmetry.
Keywords: зорові викликані потенціали; мануальна асиметрія; кореляції; visual evoked potentials; manual asymmetry; correlation